2012
DOI: 10.1111/j.1439-0264.2012.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Adrenal Gland Measurements in Healthy Yorkshire Terriers and Labrador Retrievers

Abstract: An upper threshold of 7.4 mm for maximal adrenal gland diameter is commonly used to detect pituitary-dependent hyperadrenocorticism ultrasonographically in dogs. There is a substantial overlap between adrenal gland diameter of healthy dogs and of those with pituitary-dependent hyperadrenocorticism. The aim of this study is to determine the measurements of both adrenal glands, in particular, of the height at the caudal glandular pole in a longitudinal plane, in the Labrador retriever and Yorkshire terrier, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(62 citation statements)
references
References 20 publications
6
43
2
2
Order By: Relevance
“…Whether or not a relationship exists between ultrasonographically obtained adrenal gland measurements and body weight has not been clearly documented in previous reports. Discrepancies exist among earlier studies that attempted to document an association between adrenal gland measurements and body weight using ultrasonography, but Bertolini et al found no relationship between the volume of the adrenal glands and body weight using computed tomography …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not a relationship exists between ultrasonographically obtained adrenal gland measurements and body weight has not been clearly documented in previous reports. Discrepancies exist among earlier studies that attempted to document an association between adrenal gland measurements and body weight using ultrasonography, but Bertolini et al found no relationship between the volume of the adrenal glands and body weight using computed tomography …”
Section: Introductionmentioning
confidence: 99%
“…A wide range of values have been documented by previous studies with regard to normal ultrasonographic size (length, width, and thickness) of the adrenal glands in healthy dogs. Adrenal gland measurements in normal dogs have been reported to vary from 0.91 to 5.02 cm for length, from 0.19 to 1.74 cm for width, and from 0.17 to 1.07 cm for thickness/height . Additionally, although dogs with hyperadrenocorticism have adrenal gland measurements significantly greater than those of normal dogs and dogs with hypoadrenocorticism have adrenal gland measurements significantly less than those of normal dogs, an overlap in the range of measurements of dogs with either disease and normal dogs is present.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is described in the literature as a useful imaging modality in the diagnostic workup of canine patients with adrenal neoplasms of the cortex and medulla, hypoadrenocorticism or hyperadrenocorticism and aiding in differentiation of pituitarydependent hyperadrenocorticism (PDH) from adrenal-dependent hyperadrenocorticism (ADH) (Douglass et al 1997;Choi et al 2011;Chalus et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…From each US report and available US images, the following criteria were collected in an excel spreadsheet and reviewed: side and size (mm) of adrenal lesions, the dimension (mm) of the contralateral AG, echogenicity (hypoechoic, hyperechoic, or isoechoic to adjacent adipose tissue), echotexture (homogeneous, heterogeneous) and contours of the lesion (smooth or irregular), presence or absence of mineralization, and finally presence or absence of vascular invasion . The contralateral AG was considered atrophied when its maximal thickness was less than 5.0 mm . Computed tomographic reports, when available, were also reviewed, in order to complete the diagnostic workup.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 The contralateral AG was considered atrophied when its maximal thickness was less than 5.0 mm. [46][47][48] Computed tomographic reports, when available, were also reviewed, in order to complete the diagnostic workup. The revision of the US and CT images was at the discretion of the radiologist who submitted the case, if the report was not complete enough to answer to aforementioned criteria.…”
Section: Ultrasound Reports Reviewmentioning
confidence: 99%